Perceived city sustainability and tourist behavioural intentions - Conti, S.; Dias, Á.; Pereira, L. (Smart Cities, 2023)
The focus on the sustainability of tourism destinations and firms is a global trend. However, the implications of those investments in tourist behavioural intentions need further investigation. This study proposes a conceptual framework for exploring the influence of sustainability perceptions and travel behaviour on the intention to recommend and revisit. The results from structural equation modelling and importance–performance matrix analysis show a direct relationship between travel behaviour and perceived sustainability. Additionally, it shows a direct relationship between travel behaviour and perceived value, corroborating previous research on green tourists. By increasing perceived sustainability, managers and marketers can enhance their sustainability strategies based on tourists’ feedback and market the destination to more specific targets via tailored communication. Sustainability perceptions were also found to be a key driver of satisfaction and to have indirect consequences on behavioural intentions of loyalty, representing the ultimate goal of a destination.